Pelaksanaan Sistem Kewarisan Islam di Indonesia: Analisis pada Adat Mayarakat Melayu Kota Dumai - Neneng Desi Susanti; Kalijunjung Hasibuan (Hikmah, 2023)
This study aims to analyze the inheritance system that has developed in Indonesia, which focuses on the Malay community in the city of Dumai. This study chose these communities due to the strength of adat which is intersecting with the system of inheritance in Islam. The research method used is qualitative based on case studies. Traditional research informants, religious leaders, and the Malay community of Dumai City. Data collection techniques using observation interviews and documentation studies.. The results of this study indicate that theoretically the kinship system in Indonesia can be distinguished into three patterns, namely the patrilineal system, the matrilineal system, and the parental or bilateral system. Malay customary inheritance law in the city of Dumai is influenced by the partilineal kinship system, also known as the sulhu distribution system. The customary inheritance law system that is used is more Islamic law where the share of men is more than double that of women. Inheritance distribution is carried out by traditional/religious leaders and attended by heirs in family meetings. By continuing to separate high inheritance, low inheritance and the inheritance of husband and wife (parents), only after that the division of this inheritance can be distributed to their heirs based on Islamic law. However, after knowing the parts of each inheritance. By continuing to maintain the house left by the heirs and still looking after one of the parents who is still alive and helping relatives who are in need or less fortunate.